Screening of Epipremnum Sp., Syngramma alysmifolia, Thotea Sp. and Smilax Sp. for antimicrobial activity. - Nawi, Liliwirianis (IDOSI Publications, 2010)
The investigation of certain indigenous plants for their antimicrobial properties may yield useful results where the use of plant extracts and photochemical can be of great significance in therapeutic treatments. This study was conducted to screen the antimicrobial activity of the herbs crude. Four species of herbs were collected from UiTM Pahang Forest Reserve The extract were tested using blank disc of 6mm diameter with different types of concentration loaded with Epipremnum sp., Syngramma alysmifolia, Thotea sp. and Smilax sp. crude. The result revealed that Smilax sp. crude exhibit an antimicrobial activity against Escherichia coli, Bacillus subtilis, Staphylococcus aeureus, Salmonella paratyphi and Pseudomonas aeruginosa. This study implies the great potential of local plants for their usage and development of new drugs in the treatment of bacterial diseases.